2017
DOI: 10.1186/s12879-017-2435-4
|View full text |Cite
|
Sign up to set email alerts
|

Reemergence of yellow fever in Ethiopia after 50 years, 2013: epidemiological and entomological investigations

Abstract: BackgroundYellow Fever (YF) is a viral hemorrhagic disease transmitted by aedes mosquito species. Approximately, 200,000 cases and 30,000 deaths occur worldwide every year. In Ethiopia, the last outbreak was reported in 1966 with 2200 cases and 450 deaths. A number of cases with deaths from unknown febrile illness reported from South Ari district starting from November 2012. This investigation was conducted to identify the causative agent, source of the outbreak and recommend appropriate interventions.MethodsM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 11 publications
1
68
4
1
Order By: Relevance
“…Worth noting here, however, since a good number of clinical symptoms of viral hepatitis overlap with those of arboviral infections [43], involvement of the later cannot be overruled. In fact, the study area is among the known hot spots for yellow fever outbreaks [21] and is also considered to be an endemic site for many arboviral diseases because of its proximity to neighboring endemic/enzootic country Kenya, where repeated arboviral disease outbreaks have been reported [44]. Moreover, multivariate analysis also indicated that those of participants in the age group 46 to 65 years were more than thirteen times at higher risk of being positive for HCV infection as compared to those in the age group less than 18 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worth noting here, however, since a good number of clinical symptoms of viral hepatitis overlap with those of arboviral infections [43], involvement of the later cannot be overruled. In fact, the study area is among the known hot spots for yellow fever outbreaks [21] and is also considered to be an endemic site for many arboviral diseases because of its proximity to neighboring endemic/enzootic country Kenya, where repeated arboviral disease outbreaks have been reported [44]. Moreover, multivariate analysis also indicated that those of participants in the age group 46 to 65 years were more than thirteen times at higher risk of being positive for HCV infection as compared to those in the age group less than 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the inhabitants are nomadic pastoralists in the Hamer District and farmers in the Debub Ari and Bena-Tsemay districts [19]. The study districts were purposely selected because of their endemicity for yellow fever outbreaks [21], which has similar clinical features with viral hepatitis.…”
Section: Methodsmentioning
confidence: 99%
“…Its frequent presence in human-made aquatic habitats [37] indicates that a simple bifurcation between urban and rural settings may be misleading and is context dependent. Additionally, urban populations are also at increased risk of Aedes -borne diseases, which are increasing in incidence in Africa [38–41]. We regularly detected developmental stages of both An.…”
Section: Discussionmentioning
confidence: 90%
“…stephensi and Aedes in the same water body [42]. Outbreaks of chikungunya [43], dengue [44], and yellow fever [45] were recently reported from Ethiopia within the same geographic setting. The WHO recommends the use of integrated vector management [46] – an adaptive and evidence-based approach to vector control which utilizes vector control interventions from within and outside the health sector that may include larval source management of both An.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing urbanisation results in increasing human and mosquito population densities, thus establishing ideal conditions for YFV emergence and transmission [158]. The 2010 epidemic in Uganda, (the first in 15 years) served as a prelude to the outbreaks that took place in the neighbouring countries, Sudan and Ethiopia, in 2013 [86,161]. In December 2015, a large urban epidemic emerged in the Angolan capital Luanda and rapidly spread to the Democratic Republic of Congo (DRC), subsequently causing imported cases in Kenya, China and Mauritania [158,159,162,163].…”
Section: In Africamentioning
confidence: 99%